Il turismo sul movimento delle mani. Proposta di turismo accessibile per sordi in lingua dei segni (Altre Modernità, 2012)
Since a few years ago, travelling was often a dramatic experience for tourists with disabilities. Services and devices necessary to guarantee a comfortable journey usually were not made available neither by public touristic operators nor by private ones. More things must be done in the future to improve the services and devices , but the tourism concept idea has already evolved in the last ten years. The focus is now on the wellbeing of people. The first quality standard is the respect of the personal needs and the easy way to have access to all the facilities, the information and the services.In the article a proposal of accessible tourism for deaf people will be presented. Up to now, to enjoy a cultural visit, a deaf tourist usually must have to contact a specialized guide - not always available - who knows the sign language. The intent is to offer the possibility to have always access to touristic and cultural contents in a direct and complete way.We will present the first linguistic studies about sign language and its most important peculiarities. We will discuss the difference between interpretation and translation in sign language and it will presented the translation experience from Italian to Italian Sign Language (LIS) of a Venice touristic guide, that evolved in an academic spin-off project (VEASYT srl, www.veasyt.com).
Keywords: traduzione; lingua dei segni; LIS; turismo accessibile; accessibilità